PERANAN BADAN NARKOTIKA NASIONAL DALAM PENEGAKAN HUKUM DAN REHABILITASI TERHADAP PELAKU TINDAK PIDANAPENYALAHGUNAAN NARKOTIKA UNTUK DIRINYA SENDIRI SEBAGAI KORBAN (PECANDU) - NOVIKA SIMAIBANG; NURMAYA SIMANJUNTAK (JOURNAL OF LAW AND NATION, 2025)
Narcotics abuse continues to increase from year to year, not only among adults but also among teenagers and children. Given these problems, this research aims to examine and explain the function of the National Narcotics Agency in enforcing the law against individuals who carry out narcotics protection. Law enforcement as an action by BNN is expected to be able to provide answers that enable drug abusers to return to living as they should. This research method uses normative legal research. Where this research looks at various legal norms. Secondary data collected from various literature used in this research shows the role of the National Narcotics Agency in enforcing the law for narcotics perpetrators as regulated in the Narcotics Law Number 35 of 2009.